Inclusion of cinnamon and banana flavorings in the diet of weaning piglets - Moreno-Santillán, Fanny; Medina-Nicolalde, Margarita; De la Cueva-Jácome, Francisco; Vargas-Estrella, Javier; Puga-Torres, Byron Humberto (Archives of Veterinary Science, 2022)
The weaning period is one of the most critical stages in pig farming because of the stress that animals suffer when separated from their sow, along with the health challenge, fights for hierarchy, food competition and several other factors, which causes a decrease in their feed intake affecting their weight gain. Thus, the objective of this work was to determine the efficacy of including flavorings (cinnamon and banana) in the diet of recently weaned piglets on their weight gain, feed intake and feed/gain ratio. For this, 20 weaned and castrated 28-day-old male piglets weighing between 6.5 - 8 kg were randomly divided into five groups: Control treatment: unflavored food; Treatment 1: food with banana flavor; Treatment 2: food with canela flavor: Treatment 3: food with banana for 10 days - canela 10 days and banana 10 days; and Treatment 4: : food with canela for 10 days - banana 10 days and canela 10 days. The flavorings were added at 1 g/kg of the diet. The feeding period lasted 30 days for each treatment. Analysis of variance (ANOVA) was used for the statistical analysis, and differences were accepted with p <0.05. At the end of the study, it was determined that the weight gain, feed intake and feed/gain ratio were similar between the treatments (P> 0.05). From this, it can be suggested that the inclusion of flavorings (cinnamon and banana) in the diet of weaning piglets does not improve their growth performance.